Metallic oxide nanoparticles enhance chickpea resistance to root rot and wilt - Bandar ALMIMAN; Ahmed H. ZIAN; Salama A.S. EL-BLASY; Hala M. EL-GENDY; Younes M. RASHAD; Kamar M. ABD EL-HAI; Sahar A. EL-SAYED (Phytopathologia Mediterranea)
Antifungal properties of nanoparticles (NPs) of copper oxide (CuO), titanium dioxide (TiO2), and silica dioxide (SiO₂) were compared to the fungicide thiophanate-methyl for controlling root rot and wilt of chickpea, caused by, respectively, Rhizoctonia solani and Fusarium oxysporum f. sp. ciceris. Different concentrations (10, 20, or 40 ppm) of the NPs were assessed for their ability to inhibit fungal growth in vitro. All the nanoparticles had antifungal activity, with greatest effects at 40 ppm. CuO NPs at 40 ppm gave 61% reduction for Rhizoctonia rot and 65% reduction for Fusarium wilt. Alterations in the ultrastructure of the fungal mycelia were observed in response to treating with CuO NPs. No differences in in vivo tests were observed between CuO NPs and thiophanate-methyl for reducing root rot or wilt. Applications of CuO NPs also enhanced growth and yield of chickpea plants. CuO NPs had antifungal properties, increased activities of peroxidase and polyphenol oxidase in chickpea plants, and increased plant phenol contents. These results indicate that CuO NPs have potential as effective, eco-friendly alternatives to conventional fungicides for controlling of root rot and wilt of chickpea.